ANALISIS PENGANGGARAN PENJUALAN UMKM AL-FAZZA PARFUME MENGGUNAKAN METODE KUADRAT TERKECIL - Febri Khairani Harahap; Khairrul Azzahri; Luthfia Sabrina; Zainarti Zainarti (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
In this research, sales budgeting was carried out for Al-Fazza Perfume MSMEs in 2024 with the aim of evaluating budget achievements from January to May. The research method used is quantitative, using secondary data on sales of Al-Fazza Parfume during that period. Through analysis using the smallest quadrant method, a sales forecast for June 2024 was obtained of IDR 9,284,200. Sales budgeting is very important to measure business development and stability in the face of market fluctuations that may occur in the future.